Profile of Ectopic Pregnancy at Western Regional Hospital - Regmi, Rabi Prasad; Parajuly, Shyam Sundar; Shrestha, Ananda Bahadur; Singh, Dela Joshi; Gyawali, Sarvesh (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objective: Ectopic pregnancy (EP) is one of the common life threatening obstetric emergencies which if not recognized and managed on time can be ruptured which could be a cause of death. Unfortunately, the world wide incidence of EP is in an increasing trend. The main objective of this study is to assess the frequency, trends, blood loss and management aspects of EP at Western Regional Hospital (WRH), Pokhara. Materials & Methods: The study was carried out in the department of Obstetrics and Gynecolgy, WRH. Data were collected and analyzed from patient’s records and discharge summary during the period of 2072-1-1 to 2072-9-30 B.S, retrospectively. Total number of hospital deliveries (7250) during this period was obtained from record section. Diagnosis of EP was made by urine beta- hcg (human chorionic gonado-tropin hormone) test and pelvic ultrasonography. Results: The incidence of ectopic pregnancy was one in every 168 deliveries. Forty three such ectopic pregnancies were diagnosed and managed during the period, the mean age was 26.34 years, the median being the age of 25-29 years (16 patients). Twenty seven patients had ruptured ectopic pregnancy. Of all the cases, the number of patients with heterotopic pregnancy and intra uterine contraceptive device (IUCD) in situ were one for each (2.3%). All cases were satisfactorily managed with no mortality, and a mean of 6.1 days of hospital stay. Conclusion: Ectopic pregnancies are common cause of hospital admission, irrespective of patient's age all of which were managed at WRH with no mortality.